Consensual Renegotiation of Contracts in Changed Circumstances: A Comparison of Qatari, Indonesian and Saudi Civil Laws - Dawwas, Amin; Dodeen , Mahmoud (Universitas Negeri Semarang, 2025)
This paper tackles the issue of contract renegotiation due to changed circumstances that render performance of the obligor’s duties excessively onerous. Whereas Article 171(2) of the 2004 Qatar Civil Law (QCL) only acknowledges a judicial apparatus to restore contract equilibrium in changed circumstances (adaptation of contract by court), Article 97 of the 2023 Saudi Civil Transactions Law (SCTL) not only recognizes a judicial solution but also a consensual one (contract renegotiation), while the Indonesian Civil Code (ICC) fails to directly regulate hardship or consensual renegotiation. The main objective of this paper is to show the advantages of consensual renegotiation compared to adaptation of contract by court. The paper adopts descriptive, analytical, and comparative approaches to understand the reasons behind this consensual mechanism in SCTL (and QCL) and how it better serves the contracting parties’ interests. The Qatari/Saudi comparison serves as a basis for a proposed reform of the ICC. The conclusion states some important findings and recommendations. To keep the contract on solid footing and to better salvage the parties’ interests, some changes to the Qatari, Indonesian, and Saudi civil laws are proposed. The paper’s most significant recommendation is that Article QCL and ICC should expressly adopt the consensual renegotiation apparatus. Additionally, both Article 171(2) QCL and Article 97 SCTL should directly require the obligor to notify the obligee of the changed circumstances and should require the obligee to mitigate the obligor’s loss resulting from the changed circumstances. Finally, the ICC should formally adopt hardship and contract renegotiation by the parties.